Skin dose assessment using direct and indirect measurement for pregnant patient undergoing abdominal fluoroscopy procedure - Ghazali, W. N.A.W.; Mohd Noor, Noramaliza; Zurihanaz, A. A.; Rashid, N. H.A.; Khaidzir, M. S.; Shamshurim, N. (Elsevier, 2025)
Radiation exposure during complex Interventional Radiology (IR) procedures is often high, particularly in pregnant patients. It is important to monitor the patient's post-procedure condition by determining their Peak Skin Dose (PSD) value. However, direct measurements require a longer time to obtain the value. This study aimed to assess the accuracy of PSD in pregnant patients during abdominal procedures using direct and indirect measurements. PSD measurements were performed using thermoluminescent dosimeters (TLDs), Gafchromic LDV1 Film and Dose Monitoring Software (GE DoseWatch). Direct measurements were conducted using 20 sets of TLDs and a 21 cm × 30 cm LDV1 Film; placed on the patient's skin towards the X-ray tube. The patient underwent an abdominal procedure by using a Philips Allura Xper FD20/15 scanner. Indirect PSD measurements were simulated instantaneously using a GE DoseWatch. PSD distribution of TLDs revealed to be very low which is 290.23 mGy with deviation of 15.11 %, while PSD value for LDV1 Film and GE Dosewatch were 341.88 mGy and 345.44 mGy respectively with ±1.03 % percentage difference. An uncertainty of approximately ±25 % or less can be considered acceptable for PSD measurements in IR. The most accurate method for determining the PSD Value in patients is the Gafchromic LDV1 Film. The values of the radiation dose monitoring systems are comparable to those of the Gafchromic LDV1 Film, with a tolerable deviation. Thus, the dose monitoring system (GE DoseWatch) and the TLDs are reliable for determining the PSD Value for patients in the absence of Gafchromic LDV1 Film. However, the TLDs need to have some modifications to the methodology, and it is necessary to cover the whole beam during irradiation. Even though it is a high-risk procedure involving pregnant patients, PSD value for the patient was almost 0.2Gy, which is 10 % lower than the threshold value for early transient erythema symptoms (2Gy).